Elucidating the role of earth alkaline doping in perovskite-based methane dry reforming catalysts. Issue 4 (14th January 2022) - Delir Kheyrollahi Nezhad, Parastoo; Bekheet, Maged F.; Bonmassar, Nicolas; Gili, Albert; Kamutzki, Franz; Gurlo, Aleksander; Doran, Andrew; Schwarz, Sabine; Bernardi, Johannes; Praetz, Sebastian; Niaei, Aligholi; Farzi, Ali; et al.
Abstract : To elucidate the role of earth alkaline doping in perovskite-based dry reforming of methane (DRM) catalysts, we embarked on a comparative and exemplary study of a Ni-based Sm perovskite with and without Sr doping. Abstract : To elucidate the role of earth alkaline doping in perovskite-based dry reforming of methane (DRM) catalysts, we embarked on a comparative and exemplary study of a Ni-based Sm perovskite with and without Sr doping. While the Sr-doped material appears as a structure-pure Sm1.5 Sr0.5 NiO4 Ruddlesden Popper structure, the undoped material is a NiO/monoclinic Sm2 O3 composite. Hydrogen pre-reduction or direct activation in the DRM mixture in all cases yields either active Ni/Sm2 O3 or Ni/Sm2 O3 /SrCO3 materials, with albeit different short-term stability and deactivation behavior. The much smaller Ni particle size after hydrogen reduction of Sm1.5 Sr0.5 NiO4, and of generally all undoped materials stabilizes the short and long-term DRM activity. Carbon dioxide reactivity manifests itself in the direct formation of SrCO3 in the case of Sm1.5 Sr0.5 NiO4, which is dominant at high temperatures. For Sm1.5 Sr0.5 NiO4, the CO : H2 ratio exceeds 1 at these temperatures, which is attributed to faster direct carbon dioxide conversion to SrCO3 without catalytic DRM reactivity. As no Sm2 O2 CO3 surface or bulk phase as a result of carbon dioxide activation was observed for any material – in contrast to La2 O2 CO3 – we suggest that oxy-carbonate formation plays only a minor role for DRM reactivity. Rather, we identify surface graphitic carbon as the potentially reactive intermediate. Graphitic carbon has already been shown as a crucial reaction intermediate in metal-oxide DRM catalysts and appears both for Sm1.5 Sr0.5 NiO4 and NiO/monoclinic Sm2 O3 after reaction as crystalline structure. It is significantly more pronounced for the latter due to the higher amount of oxygen-deficient monoclinic Sm2 O3 facilitating carbon dioxide activation. Despite the often reported beneficial role of earth alkaline dopants in DRM catalysis, we show that the situation is more complex. In our studies, the detrimental role of earth alkaline doping manifests itself in the exclusive formation of the sole stable carbonated species and a general destabilization of the Ni/monoclinic Sm2 O3 interface by favoring Ni particle sintering.